Digital Communication as an Important Tool for Modern Librarians - Ismaya; Andi Ahmad Chabir Galib (UPT Perpustakaan UIN Alauddin Makassar, 2023)
This study aims to determine digital communication that has an important role for librarians. The research method used in this study is descriptive qualitative research, descriptive qualitative research which is meant by using literature study. Researchers collect research data through reading and recording and processing library materials. The results showed that digital communication has a very important role for modern librarians by utilizing digital communication as an important tool, librarians can improve service quality, expand user reach, build professional collaboration, and support the development of information literacy. Digital communication allows librarians to adapt to changing times and meet the needs of users in the ever-evolving digital age